Development of a sorption thermal energy storage to support the thermal management of hybrid vehicles. (18th January 2022) - Engel, Georg; Kerschenbauer, Roland; Hinteregger, Markus; Gregorcic, Gregor; Fulterer, Anna Maria; Wagner, Waldemar; Helden, Wim Van
A closed sorption thermal energy storage is developed for thermal management of hybrid vehicles. The storage is charged using waste heat of the combustion engine, and discharged to provide heating and cooling power for, e.g., battery and cabin. SAPO-34 as adsorber and different adsorber designs, including coating and granules, are assessed experimentally. A functional storage system proves a cooling power of 1 kW for 30 min (2 kW peak) in experiment. In an optimised system design, this indicates KPIs of about 27 Wh/l resp. 27 Wh/kg and 55 W/l resp. 55 W/kg for cooling. A co-simulation Trnsys/Simulink shows energy savings of 60% for cooling the battery during a worldwide harmonised light vehicles test cycle at elevated temperature levels, saving 80 s for heating a chilled battery to 20°C and saving 26 s for preheating the combustion engine to 80°C.